ANALYSIS OF INDONESIAN COFFEE EXPORT PERFORMANCE TO THE GLOBAL MARKET USING VECTOR AUTOREGRESSION (VAR) APPROACH - Zuhdi, Fadhlan; Windirah, Nola; Maulanda, Achmad Subchiandi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
Coffee is Indonesia's mainstay export commodity in the plantation sector which has provided a lot of income for Indonesia. Over time, Indonesia's coffee exports have fluctuated due to the impact of globalization and other external factors such as world coffee prices, Indonesian coffee production, the US Dollar exchange rate, Brazilian coffee exports and Colombian coffee exports. Based on this, this study aims to analyze the performance of Indonesian coffee exports to the Global Market using time series data over a period of 29 years using the Vector Autoregression (VAR) approach. The results showed that there were variables that had a short-term and unidirectional relationship with Indonesian coffee exports, namely the US Dollar exchange rate variable, Indonesian coffee production and Brazilian coffee exports.